Securing sustainability Nauru new intergenerational trust fund and beyond. (Asian Development Bank, 2017)
This brief argues that the Government of Nauru should establish a more sustainable fiscal strategy that includes increasing its savings in the new Nauru Trust Fund, and implement reforms to improve transparency and the quality of public spending.